Model nanoparticles in catalysis - Vinod, C. P.; Vysakh, A. B.; Sreedhala, S. (Metal nanoparticles and clusters: advances in synthesis, properties and applications, 2017)
The importance of surface structure in catalysis is well documented by a large volume of surface science studies carried out on single crystal surfaces. Recent years has seen rapid strides in the synthesis of structured nanomaterials with varying morphologies and architecture. There is a growing interest in utilizing model nanoparticles like morphology-controlled nanostructures and core–shell-like bimetallic nanoparticles in catalysis. Apart from showing unprecedented reactivity, they serve as a model surfaces to answer many fundamental question in catalysis and also to arrive at structure vs activity correlations in heterogeneous catalysis. This chapter gives an introduction to such nanomaterials and recent advances in utilizing these materials for catalytic applications.

Mechanistic insights into the pathways of phenol hydrogenation on Pd nanostructures - Porwa, Govind; Gupta, Shelaka; Sreedhala, S.; Elizabeth, Joes; Ithan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2019)
Product selectivity in aqueous phase phenol hydrogenation on well-defined supported Pd nanostructures (spheres, cubes, and octahedra) was studied using defined experiments and density functional theory (DFT) simulations. On Pd spheres and octahedra, the reaction initially showed high selectivity (in the first 3 h, at 363 K and 5 bar H-2 pressure) toward the partially hydrogenated product cyclohexanone. On prolonged operation (>20 h of reaction time), a shift in the product selectivity (up to 100%) toward the completely hydrogenated product cyclohexanol was observed on Pd spheres and octahedra. In contrast, the reaction on Pd cubes, which only had {100} facets, showed a high selectivity (similar to 90%) toward the product cyclohexanone even after 40 h, at the same reaction conditions. Since the {111} facets are expected to be the majority sites on a spherical particle, we attribute the selectivity trend observed on spherical Pd particles to be primarily controlled by the selectivity trend on the Pd{111} facets. This observation was further confirmed on performing the hydrogenation reaction on a mixture of Pd cube and Pd octahedron particles in a ratio of 25:75 (representing the site ratio of a spherical particle). DFT simulations provided a mechanistic insight into the reactivity of the two different facets ({100} and {111}) toward phenol hydrogenation. The calculations revealed that the selectivity significantly depended on the activation barriers involved in cyclohexanone hydrogenation on the Pd{111} facets (77 and 57 kJ/mol) as compared to those on the Pd{100} facets (97 and 101 kJ/mol).
Keywords: Cyclohexanol; cyclohexanone; facet-dependent reactivity; phenol hydrogenation

Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis

Metal deficiency tailored by the 18-electron rule stabilizes metal-based inorganic compounds - Singh, Ashutosh Kumar; Mumbaraddi, Dundappa; Mishra, Vidyanshu; Roy, Soumyabrata; Vinod, C. P.; Peter, Sebastian C. (Chemistry of Materials, 2023)
The 18-electron (18-e(-)) rule is typicallyrestrictedto predicting the stability of transition-metal-based complexes. Herein,we report the use of the 18-e(-) to predict the stabilityin a family of intermetallics MNiSn (M = V, Cr, Fe, and Co) crystallizingin the Co1.75Ge structure type. Site deficiencies at theM site obtained from single-crystal X-ray diffraction are understoodas attaining a stable noble gas electronic configuration. The densityfunctional theory -based structure calculation confirms that the deficientstructure is more stable than the ideal occupation available at thecrystal lattice. MnNiSn, which crystallizes in the half-Heusler crystalstructure, depicts the role of covalent radii of the constituent elementsin determining the crystal structure. Using X-ray absorption spectroscopyand X-ray photoelectron spectroscopy, the local structure of the above-mentionedcompounds was also elucidated, supporting the role of deficiency tunedvalence fluctuation to attain a 18-e(-) configurationthat eventually leads to the formation of stable compounds.

Morphology-dependent catalysis by Co3O4 nanostructures in atmospheric pressure carbon dioxide hydrogenation - Gupta, Sharad; Jain, Preeti; Jagadeesan, Dinesh; Vinod, C. P. (Journal of Physical Chemistry C, 2023)
In this work, three Co3O4 nanostructureswith different morphologies (cubes, rods, and sheets) were synthesizedusing a hydrothermal method and tested for the CO2 hydrogenationreaction. The physicochemical properties of the structured Co3O4 were well characterized by X-ray diffraction(XRD), Raman spectroscopy, field-emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM), high-resolution transmissionelectron microscopy (HRTEM), hydrogen temperature-programmed reduction(H-2-TPR), and X-ray photoelectron spectroscopy (XPS) techniques.Based on the characterization, cube, rod, and sheet Co3O4 nanostructures were found to expose the (100), (110),and (112) planes, respectively. The effect of cobalt oxide morphologieswith different exposed surfaces on the activity and selectivity towardCO(2) hydrogenation reaction in a plug-flow reactor operatedbetween 200 and 400 & DEG;C under atmospheric pressure conditionswas explored. The results establish a correlation of the catalyticactivity with morphological structures in the order rods > sheets> cubes. H-2-TPR and XPS studies demonstrated that thehighreducibility of Co3O4 rod makes it an excellentcatalyst for CO2 hydrogenation.